Multilayer heat-shrinkable barrier film and packages made therefrom

CN116529079BActive Publication Date: 2026-10-20CRYOVAC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180070697.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-16
Filing Date
2021-10-18
Publication Date
2026-10-20
Estimated Expiration
2041-10-18

AI Technical Summary

Technical Problem

[0007]然而,改变膜配方以改善一种膜性质通常对其他膜性质具有不利影响

Benefits of technology

[0012]在多层收缩膜的一些公开实施方案的实践中可以实现的优点是膜具有良好的收缩性、可加工性、阻挡性质和光学品质。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116529079B_ABST
    Figure CN116529079B_ABST
Patent Text Reader

Abstract

A multilayer shrink film having at least two barrier layers. The barrier layers comprise an ethylene-vinyl alcohol copolymer having an ethylene content between 27-50 mol%. The multilayer shrink film has a free shrink of at least 60%, 65%, and 70% at 85°C as measured according to ASTM D2732. The multilayer shrink film has an oxygen transmission rate of no more than: 5, 10, 15, or 20 cubic centimeters (at standard temperature and pressure) per square meter per day per 1 atmosphere of oxygen pressure differential at 0% relative humidity and 23°C as measured according to ASTM D-3985. The multilayer shrink film has a post-shrink haze of less than 50 as measured according to ASTM D1003.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This application claims priority to U.S. Provisional Patent Application Serial No. 62 / 092,632, filed October 16, 2020, entitled “Multilayer Heat-Shrinkable Barrier Film and Packages Made Therefrom,” the entire contents of which are incorporated herein by reference. Background Technology

[0003] The subject matter disclosed herein relates to heat-shrinkable thermoplastic films, and more particularly to heat-shrinkable barrier films and methods for packaging products in heat-shrinkable thermoplastic films.

[0004] Multilayer thermoplastic films are being used to package a variety of food and non-food products because they protect the items from environmental impacts during storage and distribution. Furthermore, end consumers often prefer products packaged in preferably transparent thermoplastic films, allowing for visual inspection of the contents to help ensure product quality. Therefore, optical properties are generally important for thermoplastic films used in packaging.

[0005] Other properties of membranes, such as good processability, mechanical properties, and shrinkage properties, are required for membrane manufacturing and product packaging.

[0006] For certain food packaging, the film must have good oxygen barrier properties to delay or prevent the product from oxidizing or degrading during its shelf life.

[0007] However, altering membrane formulations to improve one membrane property often has adverse effects on other membrane properties. For example, membrane properties that may contribute to good mechanical properties may also lead to undesirable reductions in membrane free shrinkage and appearance characteristics (e.g., gloss, haze, and total transmittance). Therefore, it is difficult to formulate multilayer membranes that balance all processing, mechanical, and optical properties.

[0008] Furthermore, changing the membrane formulation may pose challenges to the ability to recover multilayer membranes in conventional recycling streams.

[0009] Therefore, a membrane with good optical, mechanical, processable, barrier, and shrinkable properties is needed. A membrane that can be recycled in polyethylene recycling streams is also needed.

[0010] The above discussion provides only general background information and is not intended to be used to help determine the scope of the subject matter for which protection is sought. Summary of the Invention

[0011] A multilayer shrink film having at least two barrier layers. The barrier layers comprise an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%. The multilayer shrink film exhibits at least 60%, 65%, and 70% free shrinkage at 85°C, as measured by ASTM D2732. The oxygen permeability of the multilayer shrink film, measured at 0% relative humidity and 23°C, does not exceed: 5, 10, 15, or 20 cubic centimeters (at standard temperature and pressure) per square meter per day per atmosphere of oxygen pressure differential, as measured by ASTM D1003. The multilayer shrink film has a post-shrinkage haze of less than 50, as measured by ASTM D1003.

[0012] In practice, some publicly disclosed embodiments of multilayer shrink films offer the advantage of good shrinkage, processability, barrier properties, and optical quality.

[0013] In one exemplary embodiment, a multilayer shrink film is disclosed. The multilayer shrink film includes: a) a first outer layer as a sealant layer; b) a first barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%; c) a second barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%; d) a first connecting layer disposed between the first and second barrier layers and directly adhered to at least one of the first or second barrier layers, the connecting layer comprising at least one component selected from: anhydride-modified grafted linear low-density polyethylene, anhydride-grafted low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymer, anhydride-grafted butyl acrylate copolymer, homogeneous ethylene / α-olefin copolymer, and anhydride-grafted ethylene / vinyl acetate copolymer; and e) a second outer layer as a surface layer. The multilayer shrink film, as measured by ASTM D2732, has at least 60%, 65%, and 70% free shrinkage at 85°C; as measured by ASTM D-3985 at 0% relative humidity and 23°C, has an oxygen permeability not exceeding: 5, 10, 15, or 20 cubic centimeters (at standard temperature and pressure) per square meter per day per atmosphere of oxygen pressure difference; and as measured by ASTM D 1003, has a haze of less than 50 after shrinkage.

[0014] In another exemplary embodiment, a packaging product is disclosed. The packaging product has a multilayer shrink film and a product. The multilayer shrink film includes a) a first outer layer as a sealant layer; b) a first barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%; c) a second barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%; d) a first connecting layer disposed between the first and second barrier layers and directly adhered to at least one of the first or second barrier layers, the connecting layer comprising at least one component selected from: anhydride-modified grafted linear low-density polyethylene, anhydride-grafted low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymer, anhydride-grafted butyl acrylate copolymer, homogeneous ethylene / α-olefin copolymer, and anhydride-grafted ethylene / vinyl acetate copolymer; and e) a second outer layer as a surface layer. The multilayer shrink film, as measured by ASTM D2732, has at least 60%, 65%, and 70% free shrinkage at 85°C; as measured by ASTM D-3985 at 0% relative humidity and 23°C, has an oxygen permeability not exceeding: 5, 10, 15, or 20 cubic centimeters (at standard temperature and pressure) per square meter per day per atmosphere of oxygen pressure difference; and as measured by ASTM D 1003, has a haze of less than 50 after shrinkage.

[0015] In another exemplary embodiment, a method for manufacturing a multilayer shrink film is disclosed. The method includes the step of co-extruding a multilayer shrink film comprising: a) a first outer layer as a sealant layer; b) a first barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27 and 50 mol%; c) a second barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27 and 50 mol%; d) a first connecting layer disposed between the first and second barrier layers and directly adhered to at least one of the first or second barrier layers, the connecting layer comprising at least one component selected from: anhydride-modified grafted linear low-density polyethylene, anhydride-grafted low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymer, anhydride-grafted butyl acrylate copolymer, homogeneous ethylene / α-olefin copolymer, and anhydride-grafted ethylene / vinyl acetate copolymer; and e) a second outer layer as a surface layer. The multilayer shrink film, as measured by ASTM D2732, has at least 60%, 65%, and 70% free shrinkage at 85°C; as measured by ASTM D-3985 at 0% relative humidity and 23°C, has an oxygen permeability not exceeding: 5, 10, 15, or 20 cubic centimeters (at standard temperature and pressure) per square meter per day per atmosphere of oxygen pressure difference; and as measured by ASTM D 1003, has a haze of less than 50 after shrinkage.

[0016] This brief description of the invention is intended only to provide a brief overview of the subject matter disclosed herein according to one or more illustrative embodiments, and is not intended as a guide for interpreting the claims or for defining or limiting the scope of the invention, which is defined by the appended claims. This brief description is provided to introduce illustrative choices of concepts in a simplified form, which will be further described in the detailed description below. This brief description is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in determining the scope of the claimed subject matter. The claimed subject matter is not limited to embodiments that address any or all of the disadvantages pointed out in the background. Attached Figure Description

[0017] To understand the features of the invention, reference can be made to certain embodiments illustrated in the accompanying drawings. However, it should be noted that the drawings illustrate only certain embodiments of the invention and should not be considered as limiting its scope, which encompasses other equally effective embodiments. The drawings are not necessarily drawn to scale, and the emphasis is generally placed on features illustrating certain embodiments of the invention. Throughout the drawings, the same numerals are used to indicate the same parts. Therefore, for a further understanding of the invention, reference can be made to the following detailed description, which is read in conjunction with the accompanying drawings, in which:

[0018] Figure 1 This is a schematic diagram of the process for manufacturing a heat-shrinkable film according to one embodiment.

[0019] Figure 2 This is a schematic diagram of an end-sealed bag.

[0020] Figure 3 To pass Figure 2 The transverse cross-sectional view taken from section 3-3.

[0021] Figure 4 This is a schematic diagram of a side-sealed bag.

[0022] Figure 5 To pass Figure 4 The transverse cross-sectional view taken from section 5-5.

[0023] Figure 6 This is a cross-sectional side view of a multilayer membrane according to some embodiments. Detailed Implementation

[0024] As used herein, the term "membrane" includes plastic webs, whether they are films or sheets. The thickness of the membrane can be 0.25 mm or less, or 0.5 to 30 mils, or 0.5 to 15 mils, or 1 to 10 mils, or 1 to 8 mils, or 1.1 to 7 mils, or 1.2 to 6 mils, or 1.3 to 5 mils, or 1.5 to 4 mils, or 1.6 to 3.5 mils, or 1.8 to 3.3 mils, or 2 to 3 mils, or 1.5 to 4 mils, or 0.5 to 1.5 mils, or 1 to 1.5 mils, or 0.7 to 1.3 mils, or 0.8 to 1.2 mils, or 0.9 to 1.1 mils.

[0025] The multilayer membranes described herein may comprise at least and / or at most any of the following numbers of layers: 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, and 15 layers. As used herein, the term "layer" refers to a discrete membrane component that extends substantially co-exists with the membrane and has a substantially uniform composition. For the purposes of this application, if two or more directly adjacent layers have substantially the same composition, then those two or more adjacent layers may be considered a single layer. In one embodiment, the multilayer membrane employs microlayers. Each microlayer portion may comprise 10 to 1,000 microlayers.

[0026] The multilayer membrane described herein includes at least two barrier layers to restrict gas permeation through the membrane. The membrane may also include additional layers, for example, to increase volume, provide functionality, resistance to abuse, printability, or act as a connecting layer.

[0027] Below are some examples of combinations where letter symbols represent membrane layers. In the case of the multilayer membrane representation below, where the same letter appears more than once, each occurrence of that letter may represent the same composition or different compositions within a category that perform similar functions.

[0028] A / C / B / C / B / C / A, A / D / B / C / B / C / A, A / D / B / C / B / D / A, A / C / D / B / C / B / C / A, A / D / C / B / C / B / C / A, A / C / D / B / C / B / D / A, A / D / C / B / C / B / D / A, A / C / B / C / D / B / C / A, A / D / B / C / D / B / C / A, A / C / B / C / D / B / D / A, A / C / B / C / D / B / C / D / A, A / C / B / C / D / B / D / C / A, A / C / D / B / C / D / B / C / A, A / D / C / B / C / D / B / D / A, A / C / B / C / D / C / B / C / A, A / D / C / B / C / D / C / B / C / A, A / D / C / B / C / D / C / B / C / D / A, A / C / D / C / B / C / D / C / B / C / D / C / A, A / C / D / C / B / C / D / C / B / C / D / C / A.

[0029] “A” represents the outer layer as discussed in this article.

[0030] “B” represents a barrier layer as discussed in this article.

[0031] “C” represents an intermediate layer (e.g., a link layer) as discussed in this article.

[0032] “D” represents one or more other layers of the membrane, such as a bulk layer.

[0033] All component percentages used in this article are presented on a "by weight" basis unless otherwise specified.

[0034] outer membrane layer

[0035] The membrane described herein consists of an outer layer of sealant and a surface layer. The first outer layer is the sealant layer, and the second outer layer is the surface layer. As used herein, the terms "seal layer," "sealing layer," "heat-sealing layer," and "sealant layer" refer to the outer layer or layers involved in the sealing of the membrane with itself, with another layer of the same or another membrane, and / or with another article that is not a membrane. As used herein, the term "surface layer" refers to a membrane layer whose only one surface is directly adhered to another layer of the membrane while its other surface is exposed to the environment. The primary function of the surface layer is to provide resistance to puncture, abuse, heat, and abrasion.

[0036] As used herein, the term "heat-seal" and the expression "heat-sealing" refer to any seal between a first region of a membrane surface and a second region of a membrane surface, wherein the seal is formed by heating the regions to at least their respective seal initiation temperatures. Heat sealing is the process of joining two or more thermoplastic films or sheets by heating the areas in contact with each other to a temperature at which fusion occurs, typically with the aid of pressure. Heating can be performed by any one or more of a variety of methods, such as using heating rods, hot wires, hot air, infrared radiation, ultraviolet radiation, electron beams, ultrasound, and molten beads. Heat sealing is typically a relatively narrow seal across the membrane (e.g., 0.02 inches to 1 inch wide). A particular means of heat sealing is heat sealing made using a pulse sealing machine, which uses a combination of heat and pressure to form a seal, wherein the heating means provide brief pulses of heat while pressure is applied to the membrane by a sealing rod or sealing wire, followed by rapid cooling of the rod or wire.

[0037] The heat-sealing layer comprises thermoplastic polymers such as thermoplastic polyolefins and ionomers. In embodiments, the polymers used for the sealant layer include homogeneous ethylene / α-olefin copolymers, heterogeneous ethylene / α-olefin copolymers, ethylene homopolymers, ionomers, and ethylene / vinyl acetate copolymers. In some embodiments, the heat-sealing layer may comprise polyolefins, particularly ethylene / α-olefin copolymers. For example, polyolefins with a density of 0.88 g / cc to 0.917 g / cc, or 0.90 g / cc to 0.917 g / cc, or less than 0.92 g / cc. More particularly, the sealant layer may comprise at least one member selected from: high-density polyethylene, linear low-density polyethylene, medium-density polyethylene, low-density polyethylene, very low-density polyethylene, homogeneous ethylene / α-olefin copolymers, and polypropylene. As used herein, "polymer" refers to homopolymers, copolymers, terpolymers, etc. As used herein, "copolymer" includes copolymers, terpolymers, etc.

[0038] As used herein, the term "copolymer" refers to a polymer formed by the polymerization of at least two different monomers. For example, the term "copolymer" includes the copolymerization product of ethylene and an olefin (such as 1-octene). The term "copolymer" also includes copolymerizations of mixtures of, for example, ethylene, propylene, 1-propylene, 1-butene, 1-hexene, and 1-octene. As used herein, a copolymer identified by multiple monomers, such as "propylene / ethylene copolymer," refers to a copolymer in which any one monomer can be copolymerized at a higher weight or molar percentage than one or more other monomers. However, the first listed monomer is typically polymerized at a higher weight percentage than the second listed monomer.

[0039] As used in this article, "high-density polyethylene" (HDPE) has a density of at least 0.950 grams per cubic centimeter.

[0040] As used in this article, “medium-density polyethylene” (MDPE) has a density in the range of 0.930 to 0.950 g / cm³.

[0041] As used herein, “low-density polyethylene” (LDPE) has a density in the range of 0.910 to 0.930 g / cm³.

[0042] As used in this article, “linear low-density polyethylene” (LLDPE) has a density in the range of 0.910 to 0.930 g / cm³.

[0043] As used in this article, “Very Low Density Polyethylene” (VLDPE) has a density of less than 0.915 grams per cubic centimeter.

[0044] Unless otherwise stated, all densities in this document are measured according to ASTM D-1505.

[0045] As used herein, the term "polyolefin" refers to any polymerized olefin, which may be linear, branched, cyclic, aliphatic, substituted, or unsubstituted. More specifically, the term polyolefin includes homopolymers of olefins, copolymers of olefins, copolymers of olefins and non-olefinic comonomers that can copolymerize with olefins, such as unsaturated esters, unsaturated acids (especially α-β monocarboxylic acids), unsaturated acid anhydrides, metal neutral salts of unsaturated acids, etc. Specific examples include polyethylene homopolymers, polypropylene homopolymers, polybutene, ethylene / α-olefin copolymers, propylene / α-olefin copolymers, butene / α-olefin copolymers, ethylene / vinyl acetate copolymers, ethylene / ethyl acrylate copolymers, ethylene / butyl acrylate copolymers, ethylene / methyl acrylate copolymers, ethylene / acrylic acid copolymers, ethylene / methacrylic acid copolymers, modified polyolefin resins, ionomer resins, polymethylpentene, etc. Modified polyolefin resins include modified polymers obtained by copolymerizing homopolymers or copolymers of olefins with unsaturated carboxylic acids such as maleic acid, fumaric acid, etc., or their derivatives such as acid anhydrides, esters, or metal salts. They can also be obtained by incorporating unsaturated carboxylic acids such as maleic acid, fumaric acid, etc., or their derivatives such as acid anhydrides, esters, or metal salts into olefin homopolymers or copolymers.

[0046] As used herein, the terms "modified polymer" and more specific expressions such as "modified ethylene vinyl acetate copolymer" and "modified polyolefin" refer to such polymers having anhydride functionality, as defined above, grafted thereon and / or copolymerized thereon and / or blended thereon. Preferably, such modified polymers have anhydride functionality grafted thereon or polymerized thereon rather than merely blended thereon.

[0047] Typically, ethylene / α-olefin copolymers comprise copolymers resulting from the copolymerization of about 80 to 99 wt% ethylene and 1 to 20 wt% α-olefins. Preferably, ethylene / α-olefin copolymers comprise copolymers resulting from the copolymerization of about 85 to 95 wt% ethylene and 5 to 15 wt% α-olefins.

[0048] As used herein, "homogeneous polymer" refers to polymerization products with relatively large variations in molecular weight and compositional distribution, such as typical polymers prepared using conventional Ziegler-Natta catalysts. Homogeneous copolymers typically contain a relatively wide range of chain lengths and comonomer percentages. The molecular weight distribution (Mw / Mn) of a homogeneous copolymer is greater than 3.0.

[0049] As used herein, the term "homogeneous polymer" refers to a polymerization product with a relatively narrow molecular weight distribution and a relatively narrow compositional distribution. Homogeneous polymers can be used in various layers of multilayer heat-shrinkable films. Homogeneous polymers differ structurally from heterogeneous polymers because they exhibit a relatively uniform sequence of comonomers within the chains, a mirror image of the sequence distribution across all chains, and similarity in chain length, i.e., a narrower molecular weight distribution. Furthermore, homogeneous polymers are typically prepared using metallocene or other single-point type catalysis, rather than Ziegler-Natta catalysts. The molecular weight distribution (Mw / Mn) of homogeneous polymers is less than 3.0. More specifically, homogeneous ethylene / α-olefin copolymers can be characterized by one or more methods known to those skilled in the art, such as molecular weight distribution (Mw / Mn). w / M n Compositional distribution width index (CDBI), narrow melting point range, and single melting point behavior. Molecular weight distribution (M w / M n M, also known as "polydispersity," can be determined by gel permeation chromatography. In some embodiments, the M of homogeneous ethylene / α-olefin copolymers... w / M nLess than 2.7; in another embodiment, about 1.9 to 2.5; in yet another embodiment, about 1.9 to 2.3. The composition distribution width index (CDBI) of such homogeneous ethylene / α-olefin copolymers will typically be greater than about 70%. CDBI is defined as the weight percentage of copolymer molecules whose comonomer content is within 50% (i.e., ±50%) of the median total molar comonomer content. The CDBI of linear polyethylene without comonomers is defined as 100%. The composition distribution width index (CDBI) is determined via the temperature elution fractionation (TRBI) technique. CDBI determination clearly distinguishes homogeneous copolymers (i.e., narrow compositional distributions as typically assessed by CDBI values ​​greater than 70%) from commercially available VLDPEs that typically have wide compositional distributions as typically assessed by CDBI values ​​less than 55%. TREF data and the calculation of the CDBI of the copolymers thus determined are readily available from techniques known in the art, such as Wild et al. J. The data obtained from temperature elution fractionation as described in Poly. Sci. Poly. Phys. Ed., Vol. 20, p. 441 (1982) were calculated. In some embodiments, the CDBI of the homogeneous ethylene / α-olefin copolymer is greater than about 70%, i.e., the CDBI is about 70% to 99%. Generally, the homogeneous ethylene / α-olefin copolymers used in this invention also exhibit a relatively narrow melting point range compared to "homogeneous copolymers," i.e., polymers with a CDBI of less than 55%. In one embodiment, the homogeneous ethylene / α-olefin copolymer exhibits essentially a single melting point characteristic, as determined by differential scanning calorimetry (DSC), having a peak melting point (T0) of about 60°C to 105°C. m In one embodiment, the homogeneous copolymer has a DSC peak temperature of about 80°C to 100°C. m As used herein, the expression "essentially a single melting point" means that, as determined by DSC analysis, at least about 80% by weight of the material corresponds to a single melting point in the range of about 60°C to 105°C. m Materials with peaks and essentially no substantial fraction have peak melting points exceeding approximately 115 °C. DSC measurements were performed on a Perkin Elmer System 7 thermal analysis system. The reported melting information is the second melt data, obtained by heating the sample at a programmed rate of 10 °C / min to a temperature below its critical range. The sample was then heated again at a programmed rate of 10 °C / min (second melt).

[0050] Homogeneous ethylene / α-olefin copolymers are typically prepared by copolymerizing ethylene with any one or more α-olefins. In some embodiments, the α-olefin is C3-C. 20 α-Monoolefin, C4-C 12α-Monoolefins, C4-C8 α-monoolefins. In one embodiment, the α-olefin copolymer comprises at least one member selected from: butene-1, hexene-1, and octene-1, i.e., 1-butene, 1-hexene, and 1-octene, respectively. In one embodiment, the α-olefin copolymer comprises a blend of octene-1 and / or hexene-1 and butene-1. In another embodiment, the α-olefin copolymer comprises a blend of at least two of octene-1, hexene-1, and butene-1.

[0051] In one embodiment, the heat-sealing layer is primarily composed of polyolefins. In another embodiment, based on the total composition of the heat-sealing layer, the heat-sealing layer has a total polyolefin content of 90 to 99% by weight. In other embodiments, the heat-sealing layer is composed of polyolefins only.

[0052] In one embodiment, the melting point of the heat-sealing layer is less than any of the following values: 220°C, 210°C, 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, and 130°C; and the melting point of the heat-sealing layer may be at least any of the following values: 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C. In one embodiment, the heat-sealing layer comprises 80 to 99% by weight of a linear low-density polyethylene copolymer with a melting point between 90 and 130°C. In one embodiment, the heat-sealing layer comprises 80 to 99% by weight of an extremely low-density polyethylene copolymer with a melting point between 85 and 125°C. All references to polymers, resins, or films in this application refer to the melt peak temperature of the primary melting stage of the polymer, resin, or layer, as determined by differential scanning calorimetry according to ASTM D-3418.

[0053] In embodiments where the heat-sealing layer comprises an amorphous material, the heat-sealing layer may not clearly display a melting point. The glass transition temperature of the heat-sealing layer can be less than any of the following values ​​and can be between any of the following values: 125°C, 120°C, 110°C, 100°C, 90°C, 80°C, 70°C, 60°C, and 50°C; measured with relative humidity that can be any of the following values: 100%, 75%, 50%, 25%, and 0%. The glass transition temperature (Tg) of all mentioned polymers is... g All were determined by Perkin Elmer “half Cp extrapolated” (the point on the “half Cp extrapolated” report curve where the change in specific heat is half that of the complete transformation) according to ASTM D3418 “Standard Test Method for Transformation Temperature of Polymers by Thermal Analysis”, the full text of which is incorporated herein by reference.

[0054] In one embodiment, the heat seal layer has a melt index or composite melt index of at least 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5 and 5.0 g / 10min at 190°C and 2.16 kg.

[0055] The thickness of the heat-sealing layer can be selected to provide sufficient material to induce a strong heat-sealed bond without being so thick as to adversely affect the film properties to an unacceptable level. The thickness of the heat-sealing layer can be at least any of the following values: 0.05 mil, 0.1 mil, 0.15 mil, 0.2 mil, 0.25 mil, 0.3 mil, 0.35 mil, 0.4 mil, 0.45 mil, 0.5 mil, and 0.6 mil. The thickness of the heat-sealing layer can be less than any of the following values: 5 mil, 4 mil, 3 mil, 2 mil, 1 mil, 0.7 mil, 0.5 mil, and 0.3 mil. The thickness of the heat-sealing layer as a percentage of the total film thickness can be less than any of the following values: 50%, 40%, 30%, 25%, 20%, 15%, 10%, and 5%; and can be between any of the foregoing values ​​(e.g., 10% to 30%).

[0056] The surface layer is a membrane layer on which only one surface is directly adhered to another layer of the membrane, while the other surface is exposed to the environment. The main functions of the surface layer are to provide resistance to puncture, abuse, heat, and abrasion.

[0057] As used herein, the term "direct adhesion" applied to membrane layers is defined as adhesion between a host membrane layer and a guest membrane layer without any connecting layer, adhesive, or other layer in between. In contrast, as used herein, the term "between" applied to membrane layers expressed as being between two other specific layers includes both direct adhesion between the host layer and the two other layers therebetween, and direct adhesion not to any one or both of the two other layers therebetween, i.e., one or more additional layers may be applied between the host layer and one or more layers therebetween.

[0058] The thickness of the surface layer can be selected to provide sufficient resistance to abuse. The surface layer thickness can be at least any of the following values: 0.05 mil, 0.1 mil, 0.15 mil, 0.2 mil, 0.25 mil, 0.3 mil, 0.35 mil, 0.4 mil, 0.45 mil, 0.5 mil, and 0.6 mil. The surface layer thickness can be less than any of the following values: 5 mil, 4 mil, 3 mil, 2 mil, 1 mil, 0.7 mil, 0.5 mil, and 0.3 mil. The surface layer thickness as a percentage of the total membrane thickness can be less than any of the following values: 50%, 40%, 30%, 25%, 20%, 15%, 10%, and 5%; and can be between any of the foregoing values ​​(e.g., 10% to 30%).

[0059] In some embodiments, the surface layer comprises a polyolefin, a polypropylene copolymer, a polyolefin block copolymer, or a blend thereof. In some embodiments, the surface layer is primarily a polypropylene copolymer. In some embodiments, the surface layer comprises at least 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, or 95 wt% of a polypropylene copolymer, or substantially all of a polypropylene copolymer. In some embodiments, the surface layer comprises at least 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, or 95 wt% of LLDPE, VLDPE, or a blend thereof, or substantially all of LLDPE, VLDPE, or a blend thereof.

[0060] Connection layer

[0061] A membrane may include one or more intermediate layers, such as connecting layers. In addition to a first intermediate layer, a membrane may include a second intermediate layer. As used herein, “intermediate” refers to a layer in a multilayer membrane located between the outer and inner layers. As used herein, “inner layer” refers to a layer that is not an outer or surface layer and whose two main surfaces are directly adhered to another layer of the membrane. As used herein, “outer layer” refers to any membrane layer whose fewer than two main surfaces are directly adhered to another layer of the membrane. All multilayer membranes have two and only two outer layers, each with one main surface adhered to only one other layer of the multilayer membrane. In a single-layer membrane, there is only one layer, which is, of course, the outer layer, because neither of its two main surfaces is adhered to another layer of the membrane. “Outer layer” is also used to describe the outermost layer of multiple concentrically arranged layers in a seamless tube or the outermost layer of a seamless membrane tube.

[0062] In an implementation having multiple intermediate layers, the composition, thickness, and other characteristics of the second intermediate layer may be substantially the same as, or may be different from, any of the first intermediate layers.

[0063] An intermediate layer may, for example, be located between a heat-sealing layer and a barrier layer. An intermediate layer may be directly adjacent to the heat-sealing layer, such that there is no layer between the intermediate layer and the heat-sealing layer. An intermediate layer may be directly adjacent to the barrier layer, such that there is no layer between the intermediate layer and the barrier layer. An intermediate layer may be directly adjacent to both the heat-sealing layer and the barrier layer.

[0064] The interlayer may have a thickness of at least about and / or at most about any of the following: 0.05, 0.1, 0.15, 0.2, 0.25, 0.5, 1, 2, 3, 4, and 5 mils. The thickness of the interlayer as a percentage of the total film thickness may be at least about and / or at most about any of the following percentages: 1%, 3%, 5%, 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50%.

[0065] The intermediate layer may contain at least about and / or at most about any of the following amounts by weight of the layer: 10%, 20%, 30%, 40%, 50%, 60%, 70%, 75%, 80%, 90%, 95%, and 99.5% of any of the linking polymers described herein.

[0066] A bonding layer is an internal membrane layer that adheres two layers together. Useful bonding polymers include thermoplastic polymers that are compatible with both the polymers of the two directly adjacent layers. This dual compatibility enhances the adhesion of the bonded layers. Bonding layers can be made of polyolefins such as modified polyolefins, ethylene / vinyl acetate copolymers, modified ethylene / vinyl acetate copolymers, and homogeneous ethylene / α-olefin copolymers. Typical bonding layer polyolefins include anhydride-modified grafted linear low-density polyethylene, anhydride-grafted (i.e., anhydride-modified) low-density polyethylene, anhydride-grafted very low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymers, anhydride-grafted butyl acrylate copolymers, homogeneous ethylene / α-olefin copolymers, and anhydride-grafted ethylene / vinyl acetate copolymers.

[0067] Barrier layer

[0068] The membrane comprises at least two barrier layers. As used herein, the terms “barrier” and “barrier layer” used to describe the membrane or membrane layer’s ability to act as a barrier against one or more gases. Oxygen permeability is one method of quantifying the effectiveness of the barrier layer. As used herein, the term “oxygen permeability” refers to the amount of oxygen permeating through a membrane according to ASTM D3985, “Standard Test Method for Oxygen Permeability Through Plastic Membranes and Sheets Using Coulomb Sensors,” the entire text of which is incorporated herein by reference.

[0069] The barrier layer comprises at least 50, 60, 70, 80, 90, or 95% by weight of an ethylene-vinyl alcohol copolymer or a blend of ethylene-vinyl alcohol copolymers. In one embodiment, the barrier layer is substantially entirely composed of an ethylene-vinyl alcohol copolymer. The ethylene content of the ethylene-vinyl alcohol copolymer affects the processability of the multilayer film and also affects oxygen permeability. Generally, a lower ethylene content results in lower orientationability of the film and may make it unprocessable at certain orientation ratios. A higher ethylene content generally improves oxygen permeability properties.

[0070] In other embodiments, the barrier layer is substantially entirely an ethylene-vinyl alcohol copolymer or a blend of ethylene-vinyl alcohol copolymers. The ethylene content of the ethylene-vinyl alcohol copolymer can be about 38 mol%, or at least about any of the following values: 20%, 25%, 30%, 38%, 44%, and 48%, all molar percentages. In embodiments, the ethylene content of the ethylene-vinyl alcohol copolymer can be up to about any of the following values: 50%, 48%, 44%, 40%, and 38%, all molar percentages. In embodiments, the ethylene-vinyl alcohol copolymer or blend of ethylene-vinyl alcohol copolymers results in an ethylene content between 27 and 48 mol%. The ethylene-vinyl alcohol copolymer can include saponified or hydrolyzed ethylene / vinyl acetate copolymers, such as those with a degree of hydrolysis of at least about any of the following values: 50%, 85%, 95%, and 95%. The ethylene-vinyl alcohol copolymer can have an ethylene content of about 20 mol% to about 50 mol%. Exemplary ethylene-vinyl alcohol copolymers include those with ethylene contents of 27, 29, 32, 35, 38, 44, 48 and 50 mol% and their blends.

[0071] In one embodiment, the multilayer film includes at least two barrier layers with the same composition. In another embodiment, the multilayer film includes at least two barrier layers with different compositions.

[0072] The composition, thickness, and other properties of a barrier layer can be substantially the same as any of the other barrier layers, or they can be different from any other barrier layer.

[0073] The barrier layer may have a thickness of at least about and / or at most about any of the following: 0.05, 0.1, 0.15, 0.2, 0.25, 0.5, 1, 2, 3, 4, and 5 mils. In one embodiment, the barrier layer is less than 15% by weight of the multilayer film. In other embodiments, the barrier layer is less than 10% by weight of the multilayer film. In still other embodiments, the barrier layer is less than 5% by weight of the multilayer film.

[0074] Fill layer

[0075] The membrane may include one or more other layers, such as filler layers. Filler layers are typically one or more layers of the membrane that can increase the membrane's resistance to abuse, toughness, or modulus. In some embodiments, the membrane includes filler layers that act to increase the membrane's resistance to abuse, toughness, and / or modulus. Filler layers typically contain polymers that are inexpensive compared to other polymers in the membrane that provide some specific purpose unrelated to resistance to abuse, modulus, etc. In one embodiment, the filler layer contains at least one member selected from: ethylene / α-olefin copolymers, ethylene homopolymers, propylene / α-olefin copolymers, propylene homopolymers, and combinations thereof.

[0076] The filler layer may have a thickness of at least about and / or at most about any of the following: 0.05, 0.1, 0.15, 0.2, 0.25, 0.5, 1, 2, 3, 4, and 5 mils. The thickness of the filler layer as a percentage of the total film thickness may be at least about and / or at most about any of the following percentages: 1%, 3%, 5%, 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50%.

[0077] In the implementation, the filler layer comprises a blend of incompatible polymers. The blend of incompatible polymers can enhance the film's tear initiation, tear propagation, and linear tear properties, including the ability to manually tear along the entire length of the package made from the packaging article comprising the multilayer packaging film or across the entire width of the package made from the packaging article comprising the multilayer packaging film, i.e., the ability to tear the seal and tear all the way to the opposite side of the package. For packages made from end-sealed bags, a machine-directed tear can be manually initiated in the bag skirt, and this machine-directed tear can be manually propagated through the seal and along the length of the bag to the entire length of the package, i.e., propagating to the packaging portion corresponding to the opposite side of the package after the packaging article has been used to make the package. For packages made from side-sealed bags, a machine-directed tear can be manually initiated in the bag skirt, and this machine-directed tear can be manually propagated through the skirt and through the associated heat seal, after which the tear propagates in the machine direction across the entire width of the package, i.e., propagating to the packaging portion corresponding to the opposite side of the side-sealed bag after the packaging article has been used to make the package.

[0078] In an embodiment, the blend of incompatible polymers comprises an ethylene / α-olefin copolymer, which may contain at least one member selected from: (i) an ethylene / hexene copolymer with a density of about 0.90 g / cc to about 0.925 g / cc, and (ii) an ethylene / octene copolymer with a density of about 0.90 g / cc to about 0.925 g / cc. In other embodiments, blends of incompatible polymers include: (i) a blend of 50% by weight of a cyclic olefin copolymer and 50% by weight of a propylene homopolymer; (ii) a blend of 70% by weight of polystyrene and 30% by weight of an ethylene / vinyl acetate copolymer with a vinyl acetate content of 9% or 15%; (iii) a blend of 70% by weight of very low density polyethylene and 30% by weight of a cyclic olefin copolymer; (iv) a blend of 70% by weight of an ethylene / propylene copolymer and 30% by weight of a homogeneous ethylene / α-olefin copolymer; (v) a blend of 70% by weight of an ethylene / propylene copolymer and 30% by weight of a homogeneous ethylene / α-olefin copolymer with a vinyl acetate content of 9% or 15%. (vi) 70% by weight of ethylene / propylene copolymer and 30% by weight of ethylene / methyl acrylate copolymer; (vii) 70% by weight of polystyrene and 30% by weight of amorphous nylon; (viii) 70% by weight of ionomer resin and 30% by weight of ethylene / vinyl acetate copolymer with a vinyl acetate content of 4%; (ix) 70% by weight of polyamide and 30% by weight of low-density polyethylene; (x) 65% by weight of amorphous polyamide and 35% by weight of styrene / butadiene / styrene block copolymer.

[0079] As used herein, the term "incompatible polymers" refers to two polymers (i.e., blends of at least two polymers) that cannot form a solution or even a stable two-phase blend and tend to separate after mixing. During blending, the incompatible polymers are immiscible with each other, and the phases separate into a continuous domain and a finely dispersed discontinuous domain. The presence of one or more film layers in a blend of incompatible polymers can contribute to, enhance, or even cause linear tearing properties in multilayer heat-shrinkable films.

[0080] Multilayer film

[0081] The layers described herein constitute a multilayer membrane. The multilayer membrane possesses the desired properties. Barrier layers impart barrier properties to the multilayer membrane. In an embodiment, the oxygen permeability of the multilayer membrane structure, measured according to ASTM D-3985 at 0% relative humidity and 23°C, does not exceed: 5, 10, 15, or 20 cubic centimeters (at standard temperature and pressure) per square meter per day per atmosphere of oxygen pressure differential, which is incorporated herein by reference in its entirety. Unless otherwise stated, the OTR values ​​provided herein are measured at 0% relative humidity and 23°C.

[0082] In the implementation scheme, the oxygen permeability of the multilayer membrane, measured according to ASTM D-3985 at 90% relative humidity and 23°C, does not exceed: 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, or 70 cubic centimeters (at standard temperature and pressure) per square meter per day per atmosphere of oxygen pressure differential, the standard of which is incorporated herein by reference in its entirety. In some cases, OTR measurements at 90% relative humidity can better reproduce real-world results. Additionally, membranes exhibiting good OTR values ​​at 0% relative humidity may lose their barrier properties at higher relative humidity.

[0083] Multilayer films can also be given shrinkage characteristics by uniaxial or biaxial orientation or stretching of the film during film manufacturing. This shrinkage characteristic allows the film to shrink when exposed to heat, or, if confined, to generate shrinkage tension within the film. In a typical process, a thick structure extruded or co-extruded through an extrusion die is rapidly quenched and then heated to a suitable temperature, called the orientation temperature, which is above the glass transition temperature (Tg) of the resin used in the film itself but below the melt temperature (Tm) of at least one resin, and stretched in either or both of the machine (longitudinal) and transverse directions. As used herein, the expression “machine direction” refers to the direction along the length of the film, i.e., the film direction during the extrusion and / or coating process. As used herein, the expression “transverse direction” refers to the direction across the film, perpendicular to the machine direction or longitudinal direction. The term “extrusion” is used to describe the process of forming a continuous shape by forcing molten plastic material through a die and then cooling or chemically hardening it. A relatively high-viscosity polymer material is fed into a rotating screw with a variable pitch, i.e., an extruder, just before being extruded through a die, which forces the polymer material through the die. The term "co-extrusion" refers to the process of smoothly combining the outputs of two or more extruders in a feed block to form a multilayered flow that is fed into a die to produce a layered extrudate. Co-extrusion can be used in blown film, sheet and flat film extrusion, blow molding, and extrusion coating.

[0084] In the implementation, the multilayer film, measured according to ASTM D2732, exhibits at least 60%, 65%, and 70% free shrinkage at 85°C. As used herein, “free shrinkage” refers to the percentage change in size of a 10cm x 10cm film specimen when shrunk at 185℉, quantitatively determined according to ASTM D2732, “Standard Test Method for Unconstrained Linear Heat Shrinkage of Plastic Films and Sheets.” Unless otherwise stated, all free shrinkage values ​​disclosed herein are, of course, “total” free shrinkage values, representing the sum of (a) the percentage of free shrinkage in the longitudinal (i.e., “machine”) direction and (b) the percentage of free shrinkage in the transverse direction.

[0085] The residual force of multilayer films typically allows the packaging to remain taut and provide good presentation of the product throughout its shelf life. In embodiments, as measured according to the residual force tests described herein, the residual force of the multilayer film is at least 75, 100, 125, 150, 175, or 200 gF in either the machine direction or the transverse direction. In embodiments, as measured according to the residual force tests described herein, the residual force of the multilayer film is at least 75, 100, 125, 150, 175, or 200 gF in both the machine direction and the transverse direction. In embodiments, as measured according to ASTM D2838, the multilayer film also exhibits 10-50 kg / cm² in either the machine direction or the transverse direction. 2 The shrinkage tension between them. In the implementation, as measured according to ASTM D2838, the multilayer film also exhibits 10-50 kg / cm² in both the machine direction and the transverse direction. 2 The contraction tension between them.

[0086] One or more layers of the membrane—or at least a portion of the entire membrane—may be crosslinked, for example, to improve strength or alter the membrane's melting or softening properties. Crosslinking can be achieved by using chemical additives or by subjecting one or more membrane layers to one or more energy-based irradiation treatments—such as ultraviolet radiation or ionizing radiation such as X-rays, gamma rays, beta rays, and high-energy electron beams—to induce crosslinking between molecules of the irradiated material. Useful ionizing radiation doses include at least about and / or at most about any of the following doses: 5, 7, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 90, 100, 110, 120, 130, and 150 kGy (kilogras). In one embodiment, the membrane is irradiated to a level of 20 to 80 kGy. In another embodiment, the membrane is irradiated to a level less than 50 kGy. In yet another embodiment, the membrane is irradiated to a level less than 40 kGy. Crosslinking can be performed before the orientation process, for example, to enhance the strength of the membrane before orientation, or it can be performed after the orientation process. Insufficient crosslinking in the membrane may result in poor puncture resistance, tensile strength, elongation at break, free shrinkage, processability, machinability, and other physical properties. However, excessive crosslinking may adversely affect the recyclability of the multilayer membrane.

[0087] It may be desirable to avoid irradiating one or more film layers. To do this, one or more layers can be extruded and irradiated, and subsequent layers can then be applied to the irradiated substrate, for example, by extrusion coating. This will produce an extrusion-coated interface in which at least one layer is substantially uncrosslinked.

[0088] The multilayer film exhibits good optical properties both before and after shrinking. Furthermore, in packaged products, the film exhibits low haze both above the product area and in the packaging area outside the seal. Film haze and gloss were tested before and after shrinking by preparing 10cm x 10cm film samples and shrinking them at 185℉ as described in ASTM D2732.

[0089] Film haze values ​​were measured according to ASTM D 1003-00, "Standard Test Method for Haze and Light Transmittance of Transparent Plastics," published in July 2000, the full text of which is incorporated herein by reference. Results are reported herein as "haze percentage." Using ASTM D 1003-00, multilayer heat-shrinkable films may exhibit haze of less than 50%, less than 45%, less than 40%, or less than 35% after shrinkage. Haze results were also measured by packaging the product within the film as described herein.

[0090] The film gloss values ​​were measured according to ASTM D 2457-97, "Standard Test Method for Specular Gloss of Plastic Films and Solid Plastics," published on January 10, 1997, the full text of which is incorporated herein by reference. Results are reported in this document as "gloss percentage." When measured using ASTM D 2457-97, the film may exhibit a gloss level of 60 to 100 or 70 to 90.

[0091] In embodiments, the amount of polyamide contained in the membrane is limited to contribute to the recyclability of the membrane. In embodiments, the multilayer shrink film has less than 5, 3, or 1% polyamide by weight. In other embodiments, the multilayer shrink film is substantially free of polyamide. "Polyamide" herein refers to a polymer having amide bonds along its molecular chain, and preferably refers to synthetic polyamides such as nylon. Furthermore, such a term encompasses polymers comprising repeating units derived from monomers (such as caprolactam) that polymerize to form polyamides, polymers of diamines and diacids, and copolymers of two or more amide monomers, including nylon terpolymers, sometimes referred to in the art as "copolyamides." In embodiments, the multilayer film has a total polyolefin content of at least 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95% by weight.

[0092] The Association of Plastic Recyclers provides guidelines for determining the recyclability of polyethylene-containing films. The contents of both the “APR Benchmark Polyethylene (PE) Films and Flexible Packaging Innovation Test Protocol” (document number FILMS1-BG01, published or revised on October 24, 2018) and the “Critical Guidance Protocol for PE Film and Flexible Packaging” (document number FPE-CG-01, revised on August 31, 2020) are incorporated herein by reference. Various film concentration blends (e.g., F-12.5% ​​and F-25%) are prepared and compared with a control. The physical properties of the blown film are compared with those of the control film. There are different methods for selecting the control film. In one embodiment, the control is selected by choosing the polyolefin present at the maximum weight percentage of the multilayer shrink film. Then, the polyolefin present at its maximum weight percentage is selected as the polyolefin to be used to make the control film. This control film is a 100% multilayer shrink film containing polyolefin at its maximum weight percentage. The test procedure and physical properties are then prepared as described in the APR Benchmark Polyethylene (PE) Film and Flexible Packaging Innovation Test Procedure or the Key Guideline Procedure for PE Film and Flexible Packaging.

[0093] In another embodiment, a control is selected to more closely mimic the multilayer shrink film. This control film is made using all the polyolefins found in the multilayer shrink film. The control film is a blend of all the polyolefins contained in the multilayer shrink film. The ratio of the blend of all polyolefins in the control film is selected to mirror the polyolefin blend of the test film. In one embodiment, the ratio of the blend of all polyolefins in the control film differs from the ratio of the polyolefin blend in the multilayer shrink film by no more than 5%. The blend ratio is calculated based on the weight % of polyolefins in the multilayer shrink film and ignores all non-polyolefins contained in the multilayer shrink film. For example, if the test film contains 50% LDPE, 20% LLDPE, 20% MDPE, and 10% EVOH, the control film would contain 55.6% LDPE, 22.2% LLDPE, and 22.2% MDPE.

[0094] Once the control and test films (e.g., F-12.5% ​​and F-25%) are prepared, physical properties are measured. The differences in physical properties between the test films (e.g., F-12.5% ​​and F-25%) and the control film (F-0%) are measured. In an embodiment, the tensile strength at break of the test films containing multilayer films (e.g., F-12.5% ​​and F-25%) is no greater than Δ35%, 30%, 25%, or 20% compared to the F-0% blend of the control film, as measured according to ASTM D822. In an embodiment, the elongation at yield (MD) and elongation at TD of the test films containing multilayer films (e.g., F-12.5% ​​and F-25%) is no greater than Δ35%, 30%, 25%, or 20% compared to the F-0% blend of the control film, as measured according to ASTM D822. In the implementation scheme, measured according to ASTM D1709, the dart impact of the test membrane containing multilayer films (such as F-12.5% ​​and F-25%) is no greater than Δ35%, 30%, 25%, or 20% compared to the control membrane F-0% blend.

[0095] The multilayer films disclosed herein may have a total thickness between 1.5 and 4 mils, provided that the film provides the required properties for a particular packaging operation using the film. In one embodiment, the total thickness of the film (i.e., the combined thickness of all layers) is about 1.0 to 5 mils (1 mil is 0.001 inches); in another embodiment, it is about 1.5 to 4 mils; and in yet another embodiment, it is less than 3 mils.

[0096] Figure 1 A schematic diagram illustrating the process of producing a heat-shrinkable multilayer film according to the present invention is shown. Figure 1 In the illustrated process, solid polymer beads (not shown) are fed into multiple extruders 10 (only one extruder is shown for simplicity). Inside the extruder 10, the polymer beads are conveyed, melted, and degassed. The resulting bubble-free melt is then conveyed to a die 12 and extruded through an annular die to obtain a tube 14 with a thickness of 8 to 16 mils, or 10 to 14 mils in other embodiments, and 12 to 25 mils in still other embodiments.

[0097] After being cooled or quenched by water spray from cooling ring 16, tube 14 is folded by pinch roller 18 and then fed through an irradiation dome 20 surrounded by a protective shield 22, where tube 14 is irradiated with high-energy electrons (i.e., ionizing radiation) from the core transformer accelerator 24. Tube 14 is guided through the irradiation dome 20 on roller 26. In one embodiment, tube 14 is irradiated to a level of approximately 20 to 80 kGy. In another embodiment, tube 14 is irradiated to a level less than 50 kGy.

[0098] After irradiation, the irradiated tube 28 is guided through the pressure roller 30, whereby the tube 28 expands slightly, producing a slightly expanded tube 32 containing entrained air bubbles. However, the slightly expanded tube 32 is not significantly stretched longitudinally because the surface speed of the pressure roller 34 is approximately the same as that of the pressure roller 30. Furthermore, the slightly expanded tube 32 only expands enough to provide a substantially circular tube without significant lateral orientation, i.e., no stretching.

[0099] The slightly expanded irradiated tube 36 passes through the vacuum chamber 36 and is then conveyed through the coating die 38. A second tubular film 40 is melt-extruded from the coating die 38 and coated onto the slightly expanded irradiated tube 32, forming a multilayer tubular film 42.

[0100] After irradiation and coating, the multilayer tubular film 42 is wound onto a winding roller 44. Subsequently, in the second stage of the process of manufacturing the tubular film according to final requirements, the winding roller 44 is removed and installed as an unwinding roller 46. The multilayer tubular film 42 from the unwinding roller 46 is unwound and passed through a guide roller 50, after which the multilayer tubular film 42 is conveyed into a hot water bath 52 containing hot water 54. The now folded, irradiated, and coated tubular film 42 is immersed in the hot water 54 (with a temperature of approximately 180℉ to 210℉) for a retention time of at least approximately 5 seconds, i.e., the time period required for the film to reach the temperature required for biaxial orientation. The irradiated tubular film 42 is then guided through a pressure roller 56 and air bubbles 58 are blown in, thereby laterally stretching the tubular film 42. Furthermore, during blowing, i.e., lateral stretching, the pressure roller 60 pulls the tubular film 42 in the longitudinal direction because the surface speed of the pressure roller 60 is higher than that of the pressure roller 56. As a result of transverse stretching and longitudinal tensioning, a partially irradiated, coated, biaxially oriented blown tube film 62 is produced. This blown tube has been stretched in both the machine direction and the transverse direction, resulting in an overall orientation ratio of approximately 1:10 to 1:15. The overall orientation ratio is calculated by multiplying the film stretch ratio in the machine direction by the film stretch ratio in the transverse direction. Film stretching is determined by measuring the thickness before and after orientation. While the bubble 58 is held between the clamping rollers 56 and 60, the blown tube film 62 is folded by the roller 64, then conveyed through the pressure roller 60 and across the guide roller 66, and then wound onto the winding roller 68. The idler roller 70 ensures good winding. The term "orientation" refers to the thermoplastic web forming the film structure, wherein the web has been stretched in one direction ("uniaxial") or both directions ("biaxial") at an elevated temperature, and then fixed into an elongated configuration by cooling the material while substantially maintaining the elongated dimensions. This combination of elongation at elevated temperatures and subsequent cooling causes the polymer chains to align into a more parallel configuration, thereby altering the mechanical properties of the polymer web. Thermal shrinkage can occur when some unconstrained, unannealed, oriented polymer sheets are subsequently heated to their orientation temperature.

[0101] Figure 2 This is a schematic diagram of an end-sealed bag 70 in a flat position, which conforms to the present invention. Figure 3 To pass Figure 2 The cross-sectional view of bag 70 taken from section 3-3. Let's take a look. Figure 2 and Figure 3 The bag 70 includes a seamless tubular bag film 72 (where a top edge 74 defines a top opening), a first fold (i.e., seamless) bag side, a second fold (i.e., seamless) bag side 78, a bottom edge 80, and a transverse end seal 82, wherein the heat-sealing layer of the film self-seales to close the bottom of the bag.

[0102] Figure 4 and 5 The side-sealed bag 90 is shown, in which Figure 4 The diagram illustrates the side-sealed bag 90 in a flat position, while Figure 5 It indicates that it has passed. Figure 4 The transverse cross-sectional view of section 5-5 is shown in Figure 5-5. Please refer to it together. Figure 4 and Figure 5 The side-sealed bag 90 includes a bag film 92, a folded (i.e., seamless) bottom edge 94, a first side seal 96 and a second side seal 98, and a top edge 99 defining the top opening of the bag.

[0103] Now for reference Figure 6 It shows a cross-sectional side view of a multilayer membrane. Although a 10-layer structure is depicted, it should be understood that other layer structures beyond those shown are also included. Figure 6 The multilayer film 100 includes a first outer layer 101 as a heat-sealable layer. A filler layer 102 is directly adhered to the first outer layer 101 on one side and directly adhered to a bonding layer 103 on the other side. The multilayer film 100 includes four bonding layers 103, 105, 107, and 109. In an embodiment, the bonding layers are substantially identical in composition. In an embodiment, at least one bonding layer has a different composition from one of the adhesive layers. A first barrier layer 104 is directly adhered to the bonding layer 103 on one side and directly adhered to the bonding layer 105 on the other side. A filler layer 106 is directly adhered to the bonding layer 105 on one side and directly adhered to the bonding layer 107 on the other side. A second barrier layer 108 is directly adhered to the bonding layer 107 on one side and directly adhered to the bonding layer 109 on the other side. In an embodiment, the first and second barrier layers are substantially identical in composition. In an embodiment, the first and second barrier layers have different compositions. The connecting layer 109 is directly adhered to the second barrier layer 108 on one side and directly adhered to the outer layer 110 on the other side.

[0104] Unless otherwise stated, all references to ASTM procedures (and by reference, incorporated herein by reference) refer to the most recently published ASTM procedure up to the date of priority (i.e., original) filing of this patent application with the U.S. Patent and Trademark Office.

[0105] Example

[0106] Table I - Types of resins used in the examples

[0107]

[0108]

[0109]

[0110]

[0111] The membranes listed in Table II are as described in this article. Figure 1 The process described is as follows.

[0112] Table II Membrane Formulation

[0113]

[0114]

[0115]

[0116]

[0117]

[0118]

[0119]

[0120]

[0121]

[0122]

[0123]

[0124]

[0125]

[0126] The OTR of the membrane was measured according to Table II of ASTM D2732, and the results are reported in Table III below.

[0127] Table III-OTR

[0128]

[0129] As shown in Table IV, the membrane exhibits acceptable oxygen permeability.

[0130] Table IV - Free Contraction

[0131] Membrane 1 71% Membrane 2 88% Membrane 3 69% Membrane 4 55% Membrane 5 63% Membrane 6 58% Membrane 7 71%* Membrane 8 61%

[0132] Membranes marked with an asterisk (*) were tested directly offline and show shrinkage values ​​that are known to occasionally be higher than those of membranes tested later. Membrane 4 exhibits poor shrinkage characteristics.

[0133] Table V - Optical Properties

[0134]

[0135] Membrane haze and gloss were tested before and after shrink film preparation by preparing 10cm x 10cm membrane samples and shrinking the film at 185℉ as described in ASTM D2732.

[0136] Haze and gloss are traditionally measured on films before or after heat shrinking, but this does not describe how the packaged product will look in the packaging. Therefore, haze in the material contact area after heat treatment and haze on the skirt / header after heat treatment are measured as follows, and the results are reported in Table VI.

[0137] Sample preparation ensures a flat surface, as surface warping, ripples, or bending can severely affect test results. The test area should be free of dirt and wear.

[0138] Sample preparation

[0139] a) Prepare two bags from each membrane material, with a width 10% larger than the fluoropolymer dummy product;

[0140] b) Seal the bag near the model, leaving at least 20cm of neck space;

[0141] c) Use a metal stamp to mark a square (10×10cm) on both sides of the bag;

[0142] d) Place a Teflon model in the bag, making sure the drawn square is centered on the sample;

[0143] e) Place the package into the chamber of the vacuum sealing machine and position the product close to the sealing strip;

[0144] f) Evacuate the sample to achieve a residual vacuum of approximately 5 mbar and then apply a seal;

[0145] g) Place the sample in a steam oven at 95°C for 1 hour for heat treatment;

[0146] h) After cooling, open the seal and retrieve the bag and neck to test gloss and haze as follows.

[0147] Test program

[0148] For haze testing:

[0149] a) Place each sample (mounted in the support) against the inlet port of the instrument;

[0150] b) Measure at least three portions of the sample surface to obtain an indication of uniformity;

[0151] c) Repeat steps a) to b) for the other two samples.

[0152] Regarding the haze results:

[0153] Calculate the average, minimum, and maximum values ​​of the readings.

[0154] Report data expressed as a percentage and indicated as “haze after heat treatment”. Report results for 1) the film area in contact with the packaged material and 2) the film area in the skirt or crosshead that is not in contact with the packaged material.

[0155] Table VI - Optical Properties

[0156]

[0157] To further test optical properties, the film was evaluated by replicating haze in non-material contact areas through both water shrinkage and air shrinkage. Haze was evaluated for the non-shrink film, the film shrunken in an 85°C water bath, and the film shrunken via hot air at 110°C. The results are reported in Table VII.

[0158] Table VII - Haze Results

[0159]

[0160] Table VIII - Physical Properties

[0161]

[0162] Tensile strength, elongation at break, and Young's modulus refer to tensile properties measured according to ASTM D882, "Standard Test Method for Tensile Properties of Sheets of Plastics," the entire text of which is incorporated herein by reference. Truburst is measured according to ASTM D3786. Shrinkage tension is measured according to ASTM D2838.

[0163] Residual forces were measured at 5°C using a shrinkage tension tester that provided a constant temperature rise followed by cooling. Four specimens were prepared as rectangular strips 25.4 mm wide, and the average results are reported in Table VIII.

[0164] To test the ability of the film to be recycled in the polyethylene recycling stream, blown film samples and control films were prepared according to the guidelines provided by the Plastics Recyclers Association for determining the recyclability of polyethylene-containing films. The contents of the following documents are incorporated herein by reference: “APR Benchmark Testing Procedures for Polyethylene (PE) Films and Flexible Packaging”, document number FILMS1-BG01, published or revised on October 24, 2018; “Key Guidance Procedures for PE Films and Flexible Packaging”, document number FPE-CG-01, revised on August 31, 2020; and “APR Benchmark Testing Procedures for Polyethylene (PE) Films and Flexible Packaging”, document number FILM-B-01, published or revised in November 2020.

[0165] Control films were prepared by blending 28 wt% VLDPE2, 29 wt% VLDPE6, 17 wt% LLDPE1, and 26 wt% LLDPE5 to prepare control FOD and FOB. The remaining samples were prepared using films 7 and 8. Once the pellet and blown film samples were prepared according to the baseline and key guidelines, the samples were evaluated for several physical properties listed in Tables IX-XIII below.

[0166] Table IX-APR Test Data

[0167]

[0168] Table X-APR Test Data

[0169]

[0170]

[0171] Table XI-APR Test Data

[0172]

[0173]

[0174] (Millet) g / 10 minutes g / 10 minutes Compare with F0D MD 10.5 1.30 Compare with F0D TD 9.8 1.30 8F12.5MD membrane 14.6 1.31 8F12.5TD membrane 13.8 1.31 8F25MD membrane 15.2 1.30 0.6613 8F25TD membrane 12.1 1.30 0.6613 Compare with F0P MD 15.4 1.73 1.317 3.0623 Compare with F0P TD 13.3 1.73 1.317 3.0623 8F50MD membrane 19.9 1.73 0.2340 Membrane 8F50TD 18.4 1.73 0.2340 8F100MD membrane 26.7 1.74 0.0580 8F100TD membrane 19.6 1.74 0.0580

[0175] Table XII-APR Test Data

[0176]

[0177]

[0178] Tensile strength, elongation at break, and Young's modulus refer to tensile properties measured according to ASTM D882, "Standard Test Method for Tensile Properties of Sheets of Plastics," the full text of which is incorporated herein by reference. Melt flow was measured according to ASTM D1238, the full text of which is incorporated herein by reference.

[0179] Table XIII - Instrumented Impact Testing (ASTM D-1709)

[0180]

[0181]

[0182] This written description uses examples to disclose the invention, including the best mode, and also enables any person skilled in the art to practice the invention, including making and using any apparatus or system and performing any of the included methods. The patentable scope of the invention is defined by the claims, but may include other examples that would occur to a person skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that are not indistinguishable from the literal language of the claims, or if they include equivalent structural elements that are not substantially different from the literal language of the claims.

Claims

1. A multilayer shrink film, the multilayer shrink film comprising: a. The first outer layer of the sealant layer; b. A first barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27 and 50 mol%; c. A second barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%; d. A first connecting layer disposed between the first and second barrier layers and directly adhered to at least one of the first or second barrier layers, the first connecting layer comprising at least one component selected from: anhydride-modified grafted linear low-density polyethylene, anhydride-grafted low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymer, anhydride-grafted butyl acrylate copolymer, homogeneous ethylene / α-olefin copolymer, and anhydride-grafted ethylene / vinyl acetate copolymer; e. The second outermost layer of the surface; One of the first or second barrier layers is cross-linked and the other of the first or second barrier layers is not cross-linked; The multilayer shrink film, as measured by ASTM D2732, has at least 60% free shrinkage at 85°C; as measured by ASTM D-3985, at 0% relative humidity and 23°C, has an oxygen permeability not exceeding the oxygen pressure difference of 20 cubic centimeters per square meter per day per atmosphere at standard temperature and pressure; and as measured by ASTM D 1003, has a haze of less than 50% after shrinkage.

2. The multilayer shrink film of claim 1, wherein the first barrier layer comprises a blend of a first ethylene-vinyl alcohol copolymer having a first ethylene content and a second ethylene-vinyl alcohol copolymer having a second ethylene content, the blend producing an ethylene content between 38 and 44 mol%.

3. The multilayer shrink film of claim 1, wherein the second barrier layer comprises a blend of a first ethylene-vinyl alcohol copolymer having a first ethylene content and a second ethylene-vinyl alcohol copolymer having a second ethylene content, the blend producing an ethylene content between 38 and 44 mol%.

4. The multilayer shrink film of claim 1, wherein at least a portion of the multilayer shrink film is radiocrosslinked at a radiation dose level of less than 50 kGy.

5. The multilayer shrink film of claim 4, wherein the first barrier layer and the first outer layer are cross-linked while the second barrier layer and the second outer layer are not cross-linked.

6. The multilayer shrink film of claim 1, wherein the multilayer shrink film comprises less than 5% by weight of polyamide.

7. The multilayer shrink film of claim 1, wherein the multilayer shrink film is free of polyamide.

8. The multilayer shrink film of claim 1, wherein the first connecting layer comprises polyolefin, polyurethane, or a blend thereof.

9. The multilayer shrink film of claim 8, wherein the polyolefin comprises ethylene / unsaturated acid copolymer, ethylene / unsaturated ester copolymer, anhydride-modified polyolefin, or a blend thereof.

10. The multilayer shrink film of claim 1, wherein the tensile strength at break of the F-25% blend of the multilayer shrink film, as measured according to ASTM D882 and prepared according to the APR Standard Polyethylene Film and Flexible Packaging Innovation Test Procedure - FILMS1 - BG01, is not greater than 35% Δ compared to the F-0% blend of the control film.

11. The multilayer shrink film of claim 10, wherein the control film is a single-component polyolefin, and the polyolefin is the polyolefin constituting the multilayer shrink film by the largest weight percentage.

12. The multilayer shrink film of claim 10, wherein the control film is a blend of all polyolefins contained in the multilayer shrink film; the ratio of all polyolefins in the control film differs from the ratio of polyolefins in the multilayer shrink film by no more than 5%, wherein the ratio of the blends is calculated based on the weight % of the polyethylene copolymer in the multilayer shrink film and ignores all non-polyolefins contained in the multilayer shrink film.

13. The multilayer shrink film of claim 1, wherein the yield elongation of the F-25% blend of the multilayer shrink film, as measured according to ASTM D882 and prepared according to the APR Standard Polyethylene Film and Flexible Packaging Innovation Test Procedure - FILMS1 - BG01, is not greater than 35% Δ compared to the F-0% blend of the control film.

14. The multilayer shrink film of claim 13, wherein the control film is a single-component polyolefin, and the polyolefin is the polyolefin constituting the multilayer shrink film by the largest weight percentage.

15. The multilayer shrink film of claim 13, wherein the control film is a blend of all polyolefins contained in the multilayer shrink film; the ratio of all polyolefins in the control film differs from the ratio of polyolefins in the multilayer shrink film by no more than 5%, wherein the ratio of the blends is calculated based on the weight % of the polyethylene copolymer in the multilayer shrink film and ignores all non-polyolefins contained in the multilayer shrink film.

16. The multilayer shrink film of claim 1, wherein the melt flow rate of the P-0% blend of the multilayer shrink film prepared according to the APR Standard Polyethylene Film and Flexible Packaging Innovation Test Procedure - FILMS1 - BG01, as measured according to ASTM D1238, is at least 0.5 g / 10 min.

17. The multilayer shrink film of claim 1, wherein the total ethylene-vinyl alcohol copolymer is less than 20% by weight.

18. The multilayer shrink film of claim 1, wherein the multilayer shrink film comprises less than 5% by weight of polyvinylidene chloride.

19. The multilayer shrink film of claim 1, wherein the multilayer shrink film comprises less than 1% by weight of polyvinylidene chloride.

20. The multilayer shrink film of claim 1, wherein the multilayer shrink film is free of polyvinylidene chloride.

21. The multilayer shrink film of claim 1, wherein the first outer layer comprises LLDPE, VLDPE, LDPE, ionomer, or blend thereof.

22. The multilayer shrink film of claim 1, wherein the second outer layer comprises a polyolefin.

23. The multilayer shrink film of claim 22, wherein the second outer layer comprises a polypropylene copolymer, a polyolefin block copolymer, or a blend thereof.

24. The multilayer shrink film of claim 23, wherein the second outer layer comprises 50-95% by weight of a polypropylene copolymer and 5-50% by weight of a polyolefin block copolymer.

25. The multilayer shrink film of claim 10, wherein the control film comprises a blend of: A blend of at least 30% by weight of at least one type of very low density polyethylene or very low density polyethylene; with A blend of at least 30% by weight of at least one type of linear low-density polyethylene or linear low-density polyethylene.

26. The multilayer shrink film of claim 1, wherein the multilayer shrink film further comprises... a. A second connecting layer disposed between the first outer layer and the first barrier layer; b. A first connecting layer disposed between the first barrier layer and the inner filling layer; c. A third connecting layer disposed between the inner filling layer and the second barrier layer; d. A fourth connecting layer disposed between the second barrier layer and the second outer layer.

27. The multilayer shrink film of claim 26, wherein at least one of the first, second, third, or fourth connecting layers comprises maleic anhydride polyolefin.

28. The multilayer shrink film of claim 26, wherein the first and second connecting layers are directly adhered to the opposite surfaces of the first barrier layer and the third and fourth connecting layers are directly adhered to the opposite surfaces of the second barrier layer.

29. The multilayer shrink film of claim 1, wherein the multilayer shrink film has a total polyolefin content of at least 60% by weight.

30. The multilayer shrink film of claim 1, wherein the multilayer shrink film has a residual force of at least 70 gf in both the longitudinal and transverse directions.

31. The multilayer shrink film of claim 1, wherein, measured according to ASTM D-3985 at 90% relative humidity and 23°C, the oxygen permeability of the multilayer shrink film does not exceed an oxygen pressure difference of 70 cubic centimeters per square meter per day per atmosphere at standard temperature and pressure.

32. The multilayer shrink film of claim 1, wherein the haze of the multilayer shrink film after heat treatment in the area in contact with the packaged material is less than 10%.

33. A packaged product, the packaged product comprising: Multilayer shrink film, the multilayer shrink film comprising: a. The first outer layer of the sealant layer; b. A first barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27 and 50 mol%; c. A second barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%; d. A first connecting layer disposed between the first and second barrier layers and directly adhered to at least one of the first or second barrier layers, the first connecting layer comprising at least one component selected from: anhydride-modified grafted linear low-density polyethylene, anhydride-grafted low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymer, anhydride-grafted butyl acrylate copolymer, homogeneous ethylene / α-olefin copolymer, and anhydride-grafted ethylene / vinyl acetate copolymer; e. The second outermost layer of the surface; One of the first or second barrier layers is cross-linked and the other of the first or second barrier layers is not cross-linked; The multilayer shrink film, as measured by ASTM D2732, exhibits at least 60% free shrinkage at 85°C; as measured by ASTM D-3985, at 0% relative humidity and 23°C, its oxygen permeability does not exceed the oxygen pressure difference of 20 cubic centimeters per square meter per day per atmosphere at standard temperature and pressure; and as measured by ASTM D 1003, its haze after shrinkage is less than 50%. The product is placed inside the multi-layer shrink film.

34. The packaging product of claim 33, wherein the multilayer shrink film is a seamless plastic film tube having a first seal at one end and a second seal at the second end.

35. The packaged product of claim 34, wherein the product is disposed within the multilayer shrink film between the first and second seals and the crosshead or skirt extends away from the product beyond the first and second seals.

36. The packaging product of claim 35, wherein the haze of the heat-treated end or skirt is less than 90%.

37. The packaging product of claim 33, wherein the multilayer shrink film is shaped into a flat side-sealed bag.

38. A method for manufacturing a multilayer shrink film, the method comprising the steps of: Extruding a multilayer shrink film, the multilayer shrink film comprising: a. The first outer layer of the sealant layer; b. A first barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27 and 50 mol%; c. A second barrier layer comprising an ethylene-vinyl alcohol copolymer with an ethylene content between 27-50 mol%; d. A first connecting layer disposed between the first and second barrier layers and directly adhered to at least one of the first or second barrier layers, the first connecting layer comprising at least one component selected from: anhydride-modified grafted linear low-density polyethylene, anhydride-grafted low-density polyethylene, anhydride-grafted polypropylene, anhydride-grafted methyl acrylate copolymer, anhydride-grafted butyl acrylate copolymer, homogeneous ethylene / α-olefin copolymer, and anhydride-grafted ethylene / vinyl acetate copolymer; e. The second outermost layer of the surface; One of the first or second barrier layers is cross-linked and the other of the first or second barrier layers is not cross-linked; The multilayer shrink film, as measured by ASTM D2732, has at least 60% free shrinkage at 85°C; as measured by ASTM D-3985, at 0% relative humidity and 23°C, has an oxygen permeability not exceeding the oxygen pressure difference of 20 cubic centimeters per square meter per day per atmosphere at standard temperature and pressure; and as measured by ASTM D 1003, has a haze of less than 50% after shrinkage.

39. The method of claim 38, wherein the multilayer shrink film is irradiated at a radiation dose level of less than 50 kGy.

Citation Information

Patent Citations

  • Multilayer film having passive and active oxygen barrier layers

    CN101795864A

  • Miscible polyolefin blends with modifying polyolefin having matching segment lengths

    US5571864A